"Schooling" performance measurement: The politics of governing teacher conduct in Australia. Issue 1 (March 2015) - Henman, Paul; Gable, Alison
Highlights: Australia uses national testing to measure student, teacher and school performance. Performance data is expected to drive educational improvement at the school level. Principals' and teachers' professional goals mediate testing pressures on students. These pressures and the performance data use are shaped by school context. Rational performance data use requires a performance-ready environment. Abstract: Performance measurement (PM) in the public sector has progressively broadened to cover the operation of professionals traditionally framed as independent and autonomous. How PM reconstitutes the role and conduct of professionals is critical for understanding contemporary dynamics of policy and governance, and service provider–service user relationships. Building on Lipsky's classic Street-level Bureaucracy, this paper examines the ways in which street-level professionals are reconfigured in their roles as evidenced by the operation of Australia's schooling PM, NAPLAN. The paper reports findings from a project examining the effects of PM in social policy. Attention is given to the ambiguous and conflicting goals arising from measuring literacy and numeracy performance and the varied ways performance numbers are used by management for teacher governance at the street-level. These considerations have implications for the effectiveness of PM in delivering service improvements, the experience of service users, and the achievement of policy objectives.